Complications presented by patients with acute kidney disease that used furosemide associated or not albumin replacement (Research, Society and Development, 2020)
Acute kidney injury or acute kidney injury (AKI) is a syndrome characterized by a sudden decline in kidney function. Furosemide is the most widely used diuretic in these conditions and studies have shown that both this drug and albumin are involved in inducing diuresis and natriuresis, thus decreasing complications in the short and long term. The aim of the present study is to evaluate the complications presented by patients with AKI who used furosemide associated or not with albumin replacement in an ICU. The medical records of patients admitted to the Hospital Menandro de Farias between the years 2012 to 2017 were analyzed. Patients admitted to the ICU, regardless of the diagnosis of entry, who had taken AKI and used furosemide associated or not with albumin, were included in the study. , and who needed dialysis or not. Patients known to have chronic kidney injury were excluded from the study. Patients who used only furosemide were less submitted to hemodialysis and had higher values of urea and serum creatinine at the end of hospitalization. There was no change in the hospital outcome among patients who used furosemide alone or associated with albumin. However, individuals who used only furosemide had a lower need to undergo hemodialysis therapy.